Effect of Corporate Governance on Sustainability Disclosures: Evidence from Turkey - Şerife Önder; Renat Baimurzin (Universitas Pasundan, 2020)
This study aims to examine the relationship between the corporate governance structure and sustainability disclosure in Turkish business. To measure the impact of the board of directors on sustainability disclosure, companies on the Istanbul Stock Exchange that prepared sustainability reports per the Global Reporting Initiative (GRI) were selected as the working sample. In this study, 68 fiscal year data sets of 17 businesses that published regular sustainability reports during 2013–2016 were used. All were audited by the GRI. During the analysis, it was observed that the presence of influential community board members and the profitability of the enterprises are factors that bear positive effects on sustainability disclosures. Board size, the presence of independent board members, and the existence of corporate social responsibility committees were negative factors that, in fact, reduced sustainability disclosures of the companies. To increase sustainability disclosures, this study suggests that boards of directors should consist of influential community leaders.